PENGARUH ACTIVE STRETCHING DAN HAND EXERCISE UNTUK MENCEGAH CARPAL TUNNEL SYNDROME PADA PENDERITA DIABETES MELITUS: - Maelina Ariyanti; Heri Bahtiar; Ernawati Ernawati; Istianah Istianah; Hapipah Hapipah; Esa Maria; Aulia Septiana (Jurnal LENTERA, 2026)
Diabetes mellitus is a chronic metabolic disease that may lead to musculoskeletal complications, one of which is Carpal Tunnel Syndrome (CTS). Prolonged hyperglycemia can impair the median nerve, resulting in pain, tingling, numbness, and decreased hand function. This community service activity aimed to implement active stretching and hand exercises to reduce symptom severity and improve hand functional ability as a preventive measure against CTS in individuals with diabetes mellitus. The activity was conducted in Tanjung Village, North Lombok Regency, and involved 18 participants with diabetes mellitus. The intervention consisted of active stretching and hand exercises performed three times per week for two weeks, with a total of six sessions lasting 25 minutes each. The results showed reductions in symptom severity and hand functional impairment. Eight participants demonstrated improved hand function, while ten participants had unchanged scores. Active stretching and hand exercises contributed to reducing symptom severity and improving hand functional ability among individuals with diabetes mellitus. These exercises can be implemented as simple, safe, and easily performed non-pharmacological interventions to help reduce the risk of CTS.